ANALISIS CAPAIAN STANDAR DAN PEMANFAATAN HASIL AKREDITASI PAUD PROVINSI BANTEN - B., Busron (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2020)
Accreditation on PAUD Unit is an activity to assess the feasibility of programs and units based on eight national education standards in this case referring to Permendikbud number 137 of 2014 concerning national standards for early childhood education, accredited PAUD Units are expected to improve their quality, therefore the results of PAUD accreditation activities It needs to be analyzed and it must be useful to recommend improvements for local governments in the context of fostering the unit, while the objectives of this study are (1) how to analyze the achievement of accreditation standards in regencies / cities in Banten Province and (2) how the results of accreditation are utilized by the government regions at the district / city level in determining policies and programs. The research method used was meta-analysis using primary and secondary data. Primary data were obtained from interviews with the Chairperson of the PAUD and PNF National Accreditation Board in Banten Province. Secondary data sourced from the PAUD and PNF National Accreditation Board website, Education Data Reference Ministry of Education and Culture, as well as official laws and regulations, and related study results. The results showed that: (1) the highest average achievement of PAUD accreditation results in Banten Province in 2019 was the highest in the educational assessment standard of 91.04%, while the lowest average achievement in the content standard was 60.80% and (2) the results of accreditation have not yet been fully followed up by local governments at the district / city level.Â